Penanggulangan Kepasiran Dengan Gravel Pack Berdasarkan Sieve Analysis di Sumur A-140, Lapangan X - Deny Fatryanto Edyzoh; M. Nur Mukmin; R. Bambang Wicaksono; Engeline Marlin; Abdul Gafar Karim; Darmiyati, Iin (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2022)
This study focuses on analyzing sand grain size distribution from Well A-140 using sieve analysis to determine the optimal gravel pack size for sand control. A series of sieves with varying mesh sizes were used to separate the sand particles, and the cumulative weight of each fraction was converted into a percentage based on the total sample weight of 54.437 grams. The results revealed a relatively uniform grain size distribution, indicated by a sorting coefficient of 2.0625, classified as